Ներսես Լամբրոնացու բանաստեղծական ժառանգության հունաբանությունները - Ավետիսյան, Արփինե (Մատենադարան)
The Hellenizing language of the prominent representative of medieval Armenian literature in Cilician Armenia Nersēs Lambronats‘i (1153–1198) deserves special attention. Grecisms appeared in Armenian since the invention of the alphabet, when a great number of works were translated from Greek. But calquing Greek words and grammatical forms reached its peak in the period of the Hellenizing School (~ 570–730). The activity of the Hellenizing translators had a profound impact on the language of later authors who used various types of Grecisms in order to embellish their style. The language of Lambronats‘i’s poetical works is rich in both Grecisms created in the Classical period (which had already become common and widespread in the language) and lexical and grammatical Grecisms created in the period of the Hellenizing school. Among more than forty lexical Grecisms, there are several words created in later centuries. Most likely, two neologisms (ստորահեղուլ and տաղերգութիւն) belong to Lambronats‘i himself. Нерсес Ламбронаци (1153-1198) – выдающийся представитель армянской средневековой литературы Киликийской Армении, язык произведений которого заслуживает особого внимания. Грецизмы стали появляться в первых же армянских переводах, сделанных сразу после создания алфавита, однако калькирование греческих слов и грамматических оборотов достигло своего пика в период деятельности грекофильской школы (~ 570-730 гг.), наработки которой оказали глубокое влияние на язык более поздних авторов, использовавших разного типа грецизмы для обогащения стиля своих сочинений. В языке стихов Ламбронаци нам удалось выявить серию грецизмов как классического периода, ставших неотъемлемой частью лексики и используемых повсеместно, так и лексические и грамматические грецизмы, созданные в период расцвета грекофильской школы. В числе порядка сорока словарных грецизмов есть несколько слов, созданных в более поздний период. Два неологизма (ստորահեղուլ и տաղերգութիւն), по всей видимости, принадлежат самому Нерсесу Ламбронаци.
Keywords: Բանասիրություն; Գրականություն